2020
DOI: 10.1002/csc2.20081
|View full text |Cite
|
Sign up to set email alerts
|

Mode of reproduction and meiotic chromosome behavior in Acroceras macrum

Abstract: Acroceras macrum Stapf is a high‐quality C3 grass species adapted to the subtropics. It is a valuable forage resource in frequently flooded environments. The objectives were to analyze the type of polyploidy, mode of reproduction, and estimate seed and pollen fertility. A living collection of 22 tetraploid and five hexaploid genotypes of A. macrum was analyzed. Type of polyploidy was analyzed from chromosomal pairing at diakinesis and prometaphase I, and meiotic irregularities were evaluated during the microsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The percentage of irregular microspore tetrads in Medicago sativa L. was negatively correlated with seed fertility only when irregularity levels were high (Smith and Murphy 1986). According to Usandizaga et al (2020), meiotic irregularities are closely correlated with pollen fertility, although they do not appear to be a limiting factor for the fertility of crosses in Acroceras macrum. In the same study, pollen viability of tetraploid cytotypes with open pollination was positively correlated with the seed set (r = 43, p = 0.0034).…”
Section: Resultsmentioning
confidence: 92%
“…The percentage of irregular microspore tetrads in Medicago sativa L. was negatively correlated with seed fertility only when irregularity levels were high (Smith and Murphy 1986). According to Usandizaga et al (2020), meiotic irregularities are closely correlated with pollen fertility, although they do not appear to be a limiting factor for the fertility of crosses in Acroceras macrum. In the same study, pollen viability of tetraploid cytotypes with open pollination was positively correlated with the seed set (r = 43, p = 0.0034).…”
Section: Resultsmentioning
confidence: 92%
“…Pollen fertility analysis of different cross combinations in this study indicated that meiotic abnormalities, such as non-congression, lagging chromosomes, unequal separation and abnormal spindle fibres orientation, led to low pollen fertility. As previously reported, pollen viability is closely associated with meiosis of pollen mother cells, and meiotic abnormalities affect pollen development (Boff and Chifino-wittmann, 2002;Zha et al, 2007;Farco and Dematteis, 2014;Usandizaga et al, 2020). The relationship between meiotic abnormalities and fertility has been studied in many plant species, including Musa and Brassica (Adeleke et al, 2004;Yang et al, 2020).…”
Section: Discussionmentioning
confidence: 89%
“…However, there are multiple examples of applied research in the field of meiosis, as shown by the cytogenetic work in Mexico of Ruvalcaba‐Ruiz and Rodríguez‐Garay (2002) in blue agave, in which structural rearrangements reduce pollen fertility; the work of Usandizaga et al. (2020) in Argentina with tetraploid and hexaploid lines of forage grass Acroceras macrum Stap. ; and the work of Sattler et al.…”
Section: Meiosismentioning
confidence: 99%